Trauma-Informed Care in Education: Reflecting on School-led Interventions to Foster Community Resilience - Eithne Nic Dhomhnaill; Maria Lotty (International Journal of School Social Work, 2025)
Trauma-informed care in education and its role in fostering resilience in communities is the central theme of this article. It focuses on a three pronged approach to implementing trauma-informed practices in a DEIS primary school in Dublin, located in an area of extreme disadvantage, to support young people engaging in the process of resilience. The first trauma-informed practice adopts an ecological approach to promote community resilience, involving training for staff and community members to spread awareness and implement trauma-informed care. The second trauma-informed practice introduces a mentoring program targeting at-risk pupils in their final year of primary school. The third trauma-informed practice focuses on a peer support group for teachers, recognising the impact of vicarious trauma on educators. Challenges to the implementation of trauma-informed practice in schools are discussed, including service provider buy-in, conceptual clarity, and the lack of consistent policies. The article concludes by emphasising the importance of collaboration across services and the need for a united effort to address the complex issue of childhood trauma.
Keywords: Trauma-Informed Practice; Trauma-Informed Care; Resilience; Trauma-Informed Practices (TIPs); Trauma-Informed Schools